Validitas Arsitektur Bisnis menggunakan Metode Formal PetriNets (Studi Kasus: Perusahaan Manufaktur di Indonesia) - Fajrillah, Asti Amalia Nur; Annastasia, Syifa (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2021)
The Gartner Group estimates that 40% of all Enterprise Architecture (EA) programs discontinued due to failure to demonstrate sufficient value for the business. Business architecture has an important role to help companies achieve the desired business values. Before starting to design a business architecture, the steps that need to be done are identifying business processes, a business process is a series of activities that are interrelated to achieve certain business goals. Modelling the good business processes can help to avoid mistakes causing by quality from the beginning, further business process models have an impact on the quality of information system design. Therefore, the quality of the business process model has been recognized as an important factor for successful modelling in the company as well as the need to test the quality of business process models to keep the quality up to minimum standard. To validate the quality of business process model, we are using enterprise architecture quality framework. This framework defines the quality using certains levels, one of which uses the principle of validity with syntactical properness attribute. The syntactical properness attribute was tested through the Formal Petri nets method using WoPed tools. In this study, a case study from a manufacturing company in Indonesia is used as the test object. From the test results, 4 out of 10 business processes that has been tested did not meet the quality standards of the architectural model and improvements were made.